FEASIBILITY STUDIES ON THE TOFU INDUSTRY - Sadiq Ardo Wibowo; Citra Indah Asmarawati; Elva Susanti (Journal of Industrial Engineering Management, 2022)
Feasibility analysis is carried out in order to ascertain whether a business activity is feasible based on several aspects. In general, the aspects analyzed are technical feasibility, market feasibility, management feasibility, financial feasibility, legal feasibility and social feasibility. The financial analysis is carried out with several criteria in the form of Net Present Value (NPV), Break Even Point (BEP) and Payback Period (PP) and risk analysis. The total value of income earned per month is Rp. 80,228,000. The value of the investment interest rate is 11.4%. The analysis is carried out based on the calculation of NPV, BEP and Pacback Period so that the data knows whether this industry can be declared feasible or not. After calculating the tofu industry, the NPV value of Rp. 217,587,161. Based on this, it can be seen that this industry can provide a net income in 10 years of Rp. 217,587,161. Because the NPV value is greater than zero, this industry is declared feasible to run because it is positive. the total cost of production is Rp. 53,934,985 per month and the principal return for the selling price is Rp. 2020 per unit. Meanwhile, from the calculation of the Payback Period value in the tofu industry, it was obtained for 3.87 years, this value indicates that the business can return capital before the age of the project is over and this makes this industry also feasible to run. In risk analysis, the highest risk is on equipment and business permits. there is not any yet. Risk parameters, the equipment used is still traditional, if you want to improve, you can replace some equipment using a more automatic machine because the work process is carried out without using a division of tasks and it is better to immediately arrange for a business license